2018
DOI: 10.1136/tobaccocontrol-2017-054152
|View full text |Cite
|
Sign up to set email alerts
|

Sensory analysis of characterising flavours: evaluating tobacco product odours using an expert panel

Abstract: An expert panel was successfully trained to assess characterising odours in cigarettes and roll-your-own tobacco. This method could be applied to other product types such as e-cigarettes. Regulatory decisions on the choice of reference products and significance level are needed which directly influences the products being assessed as having a characterising odour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…An initial study was contracted to IPSOS International Market Research, Switzerland, to follow the proposed methodology. All products were tested by smokers but were smelled only as in other studies (Krüsemann et al, ).…”
Section: Results and Discussion—phase 1: Pilot Sensory Testmentioning
confidence: 99%
See 2 more Smart Citations
“…An initial study was contracted to IPSOS International Market Research, Switzerland, to follow the proposed methodology. All products were tested by smokers but were smelled only as in other studies (Krüsemann et al, ).…”
Section: Results and Discussion—phase 1: Pilot Sensory Testmentioning
confidence: 99%
“…The HETOC report and a subsequent journal article on the testing conducted to validate the descriptive method (Krüsemann et al, ) concluded that an expert panel of 18 assessors trained in 14 sessions could rate 13 attributes using smell tests. Performance was considered satisfactory, but they were not consistent for clove, coconut, tea, and vanilla.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensory assessment of tobacco products has a long history with respect to product design and consumer preference evaluation [8]. The few approaches proposed in literature for the sensory assessment of tobacco products' potentially exerting characterising flavours differ in the composition of panels, design of experiments, and statistical data evaluation [19][20][21]. The definition of characterising flavours provides conceptual challenges for both sensorial and chemical analysis [22].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of and research on e-liquid flavours can focus on consumer flavour perception (sensory science), flavouring ingredients that compose a perceived flavour (chemical analysis), and flavour descriptions that are used for marketing purposes. For example, current European and US regulations prohibit cigarettes and roll-your-own tobacco with a characterising flavour,19 20 which is monitored by a sensory panel of trained experts 21 22. Recently, more and more countries also announced regulatory actions regarding e-cigarette flavours.…”
Section: Introductionmentioning
confidence: 99%